Kinetic modeling of biomass gasification and tar formation in a fluidized bed gasifier using equivalent reactor network (ERN). (15th November 2020) - Das, Bijoy; Bhattacharya, Atmadeep; Datta, Amitava
Highlights: Kinetic modeling of biomass gasifier has been done using Equivalent Reactor Network. Formation and evolution of tar species has been analyzed using a detailed chemical mechanism. Important reactions to form specific tar species have been identified. Overall performance of the gasifier have been analyzed at different ER. Abstract: A chemical kinetic based simulation model of a bubbling fluidized bed biomass gasifier has been developed using an Equivalent Reactor Network (ERN). The pyrolysis zone is modeled using a thermodynamic equilibrium model and a kinetic-controlled perfectly stirred reactor (PSR) placed in succession. The gasification zone and the freeboard are simulated as perfectly stirred reactor (PSR) and plug flow reactor (PFR), respectively. A detailed chemical reaction mechanism is used to describe the chemistry of reaction during devolatilization and gasification stages. The formation and evolution of gaseous and tar species in different zones of the gasifier are estimated and the major reaction paths have been identified. The influence of equivalence ratio (ER) on the gasifier performance and tar species formation has been studied. Out of the three ERs considered (0.27, 0.24 and 0.19), the best performance of the gasifier is exhibited at ER = 0.24 in terms of cold gas efficiency.